A Case Report of an Unusual Presentation: Could the Early Use of Interventional Radiology have Saved this Patient of Scrub Typhus (Bangladesh Critical Care Journal, 2015)
A 19-year-old soldier was referred to our Intensive Care Unit (ICU) with a diagnosis of pyrexia of unknown origin in a state of deep coma (GCS 6/15) and shock with severe anaemia at presentation without any evidence of external or internal bleeding. He was subsequently diagnosed as a case of Scrub Typhus with Multi Organ Dysfunction (MODS). Clinical evidence of massive Gastrointestinal (GI) bleeding (melaena and clotted blood per rectum) was found next day. Despite aggressive supportive treatment we lost the patient next morning. We are presenting the case to share our experience for better management of such cases in future along with a point to ponder which probably would give an opportunity to critical care physicians to save such patients.Bangladesh Crit Care J September 2014; 2 (2): 79-80